Barometric pressure influences host-orientation behaviour in the larva of a dipteran ectoparasitoid - Crespo, José Emilio (2012)
Rain and temperature have been awarded as the most important weather factors that influence insect behavior. Barometric pressure studies have been relegated to a secondary place mainly because most studies deal with adult insects where temperature and water availability are the main environmental factors that influence behavior. We studied the influence of barometric pressure on the host orientation behavior in Mallophora ruficauda, an ectoparasitoid with an active host-seeking larval stage. Our results show that a steeper decrease in barometric pressure than expected by regular variation reduced orientation to host chemical cues. This study is the first to show a correlation between changes in the barometric pressure and the seeking behavior of parasitoid soil-dwelling larvae. Our results show that in this kind of insects, ambient factors other than temperature, water availability and light, can influence and have a profound impact on the process of parasitism. We discuss the influence of this behavior on a task so important for parasitoids as host location, and highlight the importance of including such information in parasitoid foraging ecology and climatic change studies.